(untitled) (International journal of artificial intelligence, 2025)
In today’s information-oriented society, social media has become an integral part of our daily lives. Adolescents, in particular, are among the most active users of these technologies. Adolescence is a sensitive stage in human development marked by significant psychological and social formation. During this period, adolescents strive to understand the world around them, find their place in it, and develop a unique identity. Thus, social media plays a major role in this process. The Internet is an indispensable part of modern life and is considered the most widespread global network that provides access to clear and relevant information across all fields. It enables us to understand concepts that were previously vague or difficult to grasp. There is no doubt that the demand for internet access continues to grow daily. As a global network, the Internet provides various conveniences through services in the form of text, images, audio, video, and more. At the same time, it is also true that it inadvertently draws people—especially adolescents—into a virtual world.